2016
DOI: 10.33889/ijmems.2016.1.2-008
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Calculation for Dormant k-out-of-n Systems with Periodic Maintenance

Abstract: In this paper, a dormant k-out-of-n systems redundancy calculation will be introduced. Dormant failure is a failure that cannot be detected when it occurs because of the nature of the failure characteristic. Therefore, a dormant failure becomes the blind point to the design for reliability and maintainability because of its inability to be detected. The most popular approach in detecting a dormant failure is to carry out a scheduled periodic inspection, test or maintenance activity. The scheduled periodic main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, the viewpoint of historical maintenance action here focuses on planned maintenance frequency. Research suggests that higher maintenance frequency leads to a greater effective mean time between failures (Li, 2016), but meanwhile, the corresponding periodic maintenance cost also increases. Qualitative results are expected from the evaluation to verify whether the current interval of periodic maintenance is adequate.…”
Section: Case Studymentioning
confidence: 99%
“…Therefore, the viewpoint of historical maintenance action here focuses on planned maintenance frequency. Research suggests that higher maintenance frequency leads to a greater effective mean time between failures (Li, 2016), but meanwhile, the corresponding periodic maintenance cost also increases. Qualitative results are expected from the evaluation to verify whether the current interval of periodic maintenance is adequate.…”
Section: Case Studymentioning
confidence: 99%
“…Li (2016a) compared these redundancies and found that standby redundancy is better than active redundancy. Li (2016b) also introduced the concept of dormant failure in the system. Dormant failures are those failures that cannot be detected when they occur in the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dey and Pradhan (2014) considered generalised inverted exponential distribution under hybrid censoring. These models have applications not only in the field of reliability but are also used in the system reliability as well (Li, 2016;Deepika et al, 2017;Kumar and Ram, 2018;Li et al, 2019;Chopra and Ram, 2019).…”
Section: Introductionmentioning
confidence: 99%